Patterns and Correlates of Polysubstance Use Among Individuals With Severe Alcohol Use Disorder. (21st March 2022) - Stephenson, Mallory; Aggen, Steven H; Polak, Kathryn; Svikis, Dace S; Kendler, Kenneth S; Edwards, Alexis C
Abstract: Aim: The present study examined patterns and correlates of polysubstance use among individuals with severe alcohol use disorder (AUD). Methods: Participants were 2785 individuals (63% female; mean age = 43 years, range = 18–78 years) from the Genes, Addiction and Personality Study. All participants met lifetime criteria for severe AUD (6+ symptoms). We used latent class analysis to identify patterns of frequency of lifetime use for cigarettes, marijuana, cocaine, stimulants, sedatives, opioids and hallucinogens. A variety of demographic and behavioral correlates of latent class membership were tested in univariable and multivariable models. Results: A five-class solution was selected: extended range polysubstance use (24.5%); cigarette and marijuana use (18.8%); 'testers, ' characterized by high probabilities of smoking 100 or more cigarettes, using marijuana 6+ times, and trying the remaining substances 1–5 times (12.3%); moderate range polysubstance use (17.1%) and minimal use (reference class; 27.3%). In univariable analyses, all potential correlates were related to latent class membership. In the multivariable model, associations with gender, race/ethnicity, age of onset for alcohol problems, dimensions of impulsivity, depressive symptoms, antisocial behavior and family history density of alcohol problems remained significant, though the pattern and strength of associations differed across classes. For instance, sensation-seeking, lack of premeditation and family history were uniquely associated with membership in the extended range polysubstance use class. Conclusion: Patterns of polysubstance use are differentially related to demographic and behavioral factors among individuals with severe AUD. Assessing use across multiple substances may inform the selection of targets for treatment and prevention. Abstract : Short Summary: In a sample of individuals with severe alcohol use disorder (AUD), latent class analysis (LCA) revealed five patterns of polysubstance use across seven substances. Patterns of polysubstance use were differentially related to demographic and behavioral factors, which underscores the importance of assessing use across multiple substances to inform broader treatment needs.